Socioeconomic inequalities in overweight and obesity among adults: Results from the Indonesian Food Barometer study - Siti Nurokhmah; Judhiastuty Februhartanty; Helda Khusun (PLoS ONE, 2025)
Background Globally, overweight and obesity (OAO) are significant health concerns that have detrimental effects throughout an individual’s lifetime. This study examined socioeconomic inequality in OAO among Indonesian adults. Methods Data were extracted from 1602 Indonesian adults who participated in the 2018 Indonesian Food Barometer study conducted in six provinces of Indonesia. Participants with a body mass index of 23 kg/m² or higher were classified as OAO. Socioeconomic-related inequality in OAO was estimated using the Wagstaff normalised concentration index (WCI) using wealth status and education level as the equity stratifiers. The index was further decomposed to find factors explaining the inequality. Results Of the total participants, 56.3% (95% confidence interval [CI] 52.3% to 60.2%) lived with OAO. There were more of them among poor participants (WCI −0.073, CI 95% −0.129 to −0.017) and the more educated (WCI 0.062, 95% CI 0.008–0.117). The inequality by wealth status and education level only occurred among males with WCI −0.105 (95% CI −0.207 to −0.003) and 0.224 (95% CI 0.129 to 0.306), respectively. The main contributors to these wealth-related inequalities were wealth status (79.6%), residence (81.4%) and education (29.7%), while sex and province seemed to reduce the observed inequality, with negative contributions of −20.4% and −18.7%, respectively. By education level, the observed inequality was mostly explained by education (183.1%), residence (99.4%), age (−68.6%), marital status (−45.1%), religion (42.5%), and sex (−32.1%). Conclusions Overall, we found that OAO is concentrated among the poor, but more educated population. Policies need to be developed to reduce the current burden of, and to close the socioeconomic gaps in OAO, especially among the underprivileged population and women.